Coming to Terms with the Past in Croatia : War Crimes, Victims, and Trials – Public Attitudes - Kardov, Kruno (2007)
The authors will present some of the key findings of a research on dealing with the violent past in Croatia. The results are based on a survey research carried out in 2006 on a representative sample of Croatia's majority population (N=700), and two additional samples of Serbs (N=150) and Croats (N=150) from war-torn regions. Several issues that are placed at the centre of the processes of coming to terms with the violent past will be of a particular analytical concern: attitudes towards victims, war crimes and perpetrators, and the public support for war crimes trials. The first set of problems will be discussed through the results on how different categories of war victims are perceived among Serbs, Croats and the general public. Here, we will map present problems and raise additional questions regarding the battle for recognition of the victim's status in the public sphere. The second issue will be discussed through the data that reveal different perception of Croatian and Serbian war crimes, both among the Serbs and among the Croats. The third question will deal with perception and trust in domestic and international courts for war crimes.